Treatment of Vesicoureteral Reflux after Puberty - J. Christopher Austin (Advances in Urology)
Vesicoureteral reflux is uncommonly diagnosed and treated after puberty. The natural history of uncorrected VUR after puberty is not documented. Postpubertal patients with recurrent pyelonephritis and VUR should be considered for treatment. Ureteral reimplantation, endoscopic injections, and laparoscopic or robotic ureteral reimplantation may be utilized. Endoscopic injection is an appealing option for these patients. The role of laparoscopic or robotic ureteral reimplantation in these patients is evolving.